The role of monetary policy in macroeconomic volatility of association of Southeast Asian nations-4 countries against oil price shock over time - Razmi, Fatemeh; Mohamed, Azali; Lee, Chin; Habibullah, Muzafar Shah (EconJournals, 2015)
This paper examines the impact of oil price, as a cause of economic crisis, and monetary policy through the four known channels of monetary transmission mechanism (interest rate, exchange rate, domestic credit, and stock price). Using a structural vector autoregression model based on monthly data from 2002 to 2013 for Association of Southeast Asian Nations-4 countries, oil price and monetary transmission channels are compared pre- and post-crisis. The result indicates oil price remains an important factor in explaining price volatility, even though oil price has a weaker effect compared to a stronger effect of monetary transmission mechanism on prices. Stock price for Malaysia and domestic credit for the three others can affect the prices against oil price shock. Unlike prices, the output of all countries except Thailand is more affected by oil price post-crisis compared to pre-crisis. Different monetary transmission tools affecting industrial production are compared for the four countries.